2014
DOI: 10.3892/mmr.2014.3104
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor receptor-associated factor 6 promotes migration of rheumatoid arthritis fibroblast-like synoviocytes

Abstract: Abstract. Fibroblast-like synoviocytes (FLSs) have a pivotal role in the destruction of joints in rheumatoid arthritis (RA). Tumor necrosis factor receptor-associated factor 6 (TRAF6) is a critical mediator in the inflammatory pathway and of the activity of osteoclasts. The aim of the present study was to investigate whether TRAF6 is involved in the progression of RA in mouse collagen-induced arthritis (CIA) and human RA FLSs in vitro. In vivo mouse models were transfected with TRAF6 small interfering (si)RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The mortality rate in patients with RA in China is 0.32-0.36% which is slightly lower than that of the global average (5). Due to its chronic nature and high disability rates, 75% patients with RA would become disabled in 3 years without effective and timely treatment (21). In the present study, treatment with >1 mg/kg LLDT-8 significantly reduced the clinical arthritis scores in a rat model of CIA.…”
Section: Discussionmentioning
confidence: 45%
“…The mortality rate in patients with RA in China is 0.32-0.36% which is slightly lower than that of the global average (5). Due to its chronic nature and high disability rates, 75% patients with RA would become disabled in 3 years without effective and timely treatment (21). In the present study, treatment with >1 mg/kg LLDT-8 significantly reduced the clinical arthritis scores in a rat model of CIA.…”
Section: Discussionmentioning
confidence: 45%
“…Overexpression of TRAF6 as well as enhanced TRAF6 activity have been shown to promote chronic immune stimulation in a variety of disorders, including autoimmunity, inflammation, and cancer (8). For example, it has previously been demonstrated that TRAF6 expression is elevated in rheumatoid arthritis (RA) patients (16,17) and in lupus cohorts (18). On a molecular level, disruption of TRAF6 -Ubc13 binding by the cellular protein A20 (19) or by genetic mutations (20,21) counteracts TRAF6 activity and NF-B activation.…”
Section: Constitutive Nf-b Signaling Represents a Hallmark Of Chronicmentioning
confidence: 99%
“…TRAF6 assists in the maturity of DC-mediated signal transduction and is a key to DC formation, activation, and maturation (20)(21)(22). Thus, to explore specific interventions of TRAF6 expression is essential, which inhibits DC maturation, reconstructs RA immune tolerance, and plays a therapeutic role (23,24).…”
Section: Discussionmentioning
confidence: 99%